Bilateral facial nerve palsy: a rare complication of dengue fever – a case report - Singh, Mandeep; Cheema, R K (Indian Journal of Case Reports, 2017)
Dengue is the most common mosquito-borne viral infection worldwide. There is increased evidence for dengue virus neurotropism, and neurological manifestations could make part of the clinical picture of dengue virus infection. Pathogenic mechanisms include systemic complications and metabolic disturbances resulting in encephalopathy, direct effect of the virus provoking encephalitis, and post infectious immune mechanisms causing immune-mediated syndromes. Dengue viruses should be considered as a cause of neurological disorders in endemic regions. Standardized case definitions for specific neurological complications are still needed. We report a patient with dengue fever who later developed bilateral facial nerve palsy.